Modern requirements for information graphics in research articles - Yu. V. Rodionova (Кардиоваскулярная терапия и профилактика)
In September 2021, the Russian Society for the Prevention of Noncommunicable Diseases published a practical guideline “Promoting the research results using infographic tools and graphical summaries”, which describes data visualization in research articles. The use of infographics in scientific articles becomes more and more popular. Therefore, researchers began to ask more often: how to create a graphical summary or a short presentation with the research results? The article outlines the basic principles of graphical data representation that will help authors in preparing publications.